Sejarah Mercusuar di Kampung Bojong Desa Cikoneng Kecamatan Anyer Kabupaten Serang Provinsi Banten - Septiana Septiana; Ali Imron; Suparman Arif (FKIP UNIVERSITAS LAMPUNG, 2019)
The research problem was why the lighthouse was built in Kampung Bojong, Cikoneng Village. The research was conducted to find out why the lighthouse was built in the village of Bojong, Cikoneng Village. The research method was historical research. The theoretical framework was used to explain the problems of the Dutch East Indies colonial heritage as a ship's watch tower in the waters of the Sunda Strait. It has political economic interests. The conclusion of the lighthouse signifies the existence of Banten City Port. The Dutch colonial period marked the beginning of the construction of the Pos Anyer-Panarukan Highway.Permasalahan penelitian adalah mengapa mercusuar dibangun di Kampung Bojong, Desa Cikoneng.Penelitian untuk mengetahui mengapa mercusuar dibangun di kampung Bojong Desa Cikoneng. Metode penelitian adalah penelitian sejarah. Kerangka teoritis digunakan menjelaskan permasalahan peninggalan kolonial Hindia-Belanda sebagai menara pengawas kapal laut di perairan Selat Sunda. Memiliki kepentingan politik ekonomi. Kesimpulan mercusuar penanda eksistensi Banten Kota Pelabuhan. Masa kolonial Belanda penanda awal mula pembangunan Jalan Raya Pos Anyer-Panarukan.Kata kunci: cikoneng, mercusuar, sejara